The common bean genome - Pérez de la Vega, M.; Santalla, Marta; Marsolais, Frédéric (Springer, 2017)
This book provides insights into the genetics and the latest advances in genomics research on the common bean, offering a timely overview of topics that are pertinent for future developments in legume genomics. The common bean (Phaseolus vulgaris L.) is the most important grain legume crop for food consumption worldwide, as well as a model for legume research, and the availability of the genome sequence has completely changed the paradigm of the ongoing research on the species. Key topics covered include the numerous genetic and genomic resources, available tools, the identified genes and quantitative trait locus (QTL) identified, and there is a particular emphasis on domestication. It is a valuable resource for students and researchers interested in the genetics and genomics of the common bean and legumes in general.
Keywords: Common bean -- Genetics.; elektronické knihy; electronic books